2018
DOI: 10.1255/jsi.2018.a9
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of leghaemoglobin content in pea nodules based on near infrared hyperspectral imaging spectroscopy and chemometrics

Abstract: Leghaemoglobin content in nodules is closely related to the amount of nitrogen fixed by the legume–rhizobium symbiosis. It is, therefore, commonly measured in order to assess the effect of growth-promoting parameters such as fertilisation on the symbiotic nitrogen fixation efficiency of legumes. The cyanmethaemoglobin method is a reference method in leghaemoglobin content quantification, but this method is time-consuming, requires accurate and careful technical operations and uses cyanide, a toxic reagent. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…The next group of was due to T3, T5 and T2 for the leghaemoglobin content of 1.545, 1.493 and 1.430 mg plant -1 representing 17.2, 13.3 and an 8.5% response. The finding was in support to that of Eylenbosch et al [33] that higher leghaemoglobin content was due to better root and nodule development. Dutta and Bandyopadhyay [34] reported that phosphorus and biofertilizer application increased significantly the nodulation, leghaemoglobin content, and nitrogenase activity.…”
Section: Leghaemoglobin Contentsupporting
confidence: 91%
“…The next group of was due to T3, T5 and T2 for the leghaemoglobin content of 1.545, 1.493 and 1.430 mg plant -1 representing 17.2, 13.3 and an 8.5% response. The finding was in support to that of Eylenbosch et al [33] that higher leghaemoglobin content was due to better root and nodule development. Dutta and Bandyopadhyay [34] reported that phosphorus and biofertilizer application increased significantly the nodulation, leghaemoglobin content, and nitrogenase activity.…”
Section: Leghaemoglobin Contentsupporting
confidence: 91%
“…The higher leghemoglobin contents in this treatments due to the better root and nodules development [9,10].…”
Section: Leghemoglobin Content In Soybean Nodulesmentioning
confidence: 77%
“…Warna ini menandakan adanya leghemoglobin yang berfungsi untuk mengikat oksigen (Eylenbosch et al, 2018). Oksigen tersebut dibutuhkan oleh bakteri rhizobium untuk melakukan penambatan nitrogen yang berperan dalam proses pertumbuhan (Zulkarnain, 2014).…”
Section: Simpulanunclassified